АДАПТИВНОЕ К ВАРИАЦИЯМ АКТИВНОГО СОПРОТИВЛЕНИЯ РОТОРА ВЕКТОРНОЕ УПРАВЛЕНИЕ АСИНХРОННЫМ ДВИГАТЕЛЕМ НА ОСНОВЕ НЕЛИНЕЙНОГО ПРИНЦИПА РАЗДЕЛЕНИЯ - Пересада, С.М.; Ковбаса, С.М.; Трандафилов, В.Н.; Бовкунович, В.С. (Інститут електродинаміки НАН України, Київ, 2015)
The nonlinear separation principle for adaptive with respect of rotor resistance variation indirect field oriented control of induction motors has been proven. The adaptive system is composed from globally exponentially stable torque-flux indirect controller and locally exponentially stable adaptive with respect to rotor resistance variations observer. It is shown that for bounded torque and flux reference trajectories adaptive controller with replacement of actual rotor resistance by estimated one guarantees locally asymptotically stable torque-flux tracking and resistance estimation. Correct rotor resistance estimation is achieved if persistency of excitation conditions are satisfied (electromagnetic torque is not zero or rotor flux vector modulus is not zero). Otherwise rotor current is zero and rotor resistance has no influence for system behavior. Experimentally it is shown that dynamic behavior of autonomous subsystems and in closed loop adaptive system is the same proving strong dynamic separations of the subsystems. References 6, figures 2.